Ocular Side Effects of EGFR-Inhibitor ABT-414 in Recurrent Glioblastoma: A Long-Term Safety Study - Parrozzani, Raffaele; Lombardi, Giuseppe; Midena, Edoardo; Londei, Davide; Padovan, Marta; Marchione, Giulia; Caccese, Mario; Midena, Giulia; Zagonel, Vittorina; Frizziero, Luisa (Frontiers in Oncology, 2020)
This study aimed to prospectively evaluate, on a long-term basis, corneal side effects secondary to compassionate administration of epidermal growth factor receptor (EGFR) inhibitor depatuxizumab mafodotin (ABT-414) in patients affected by EGFR-amplified recurrent glioblastoma. Fifteen patients with a median follow-up of 4.3 months after treatment discontinuation were enrolled. Each patient underwent full ophthalmologic examination including in vivo corneal confocal microscopy (CCM). No CTCAE grade 4 toxicity and four (27%) grade 3 toxicities were documented during treatment. Ocular symptoms (blurred vision, eye pain, photophobia) were experienced by all patients, reaching maximal severity after the second ABT-414 infusion, with persistence until treatment discontinuation. During treatment, CCM documented specific changes in the corneal epithelium and in the sub-basal nerve plexus layer fibers of all eyes. The median time of symptoms resolution after treatment discontinuation ranged from 38 days (eye pain) to 53 days (photophobia). The median time of signs resolution ranges from 14 days (corneal ulcer) to 38 days (superficial punctate epitheliopathy, corneal stroma edema and intraepithelial cysts). ABT-414 corneal side effects are detectable in all treated patients. Related symptoms are gradually experienced by all patients during treatment and although reversible, they are characterized by a relative prolonged persistence after treatment discontinuation.